2018
DOI: 10.1186/s12884-018-1850-x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial/venous thrombosis, fetal loss and stillbirth in pregnant women with systemic lupus erythematosus versus primary and secondary antiphospholipid syndrome: a systematic review and meta-analysis

Abstract: BackgroundWe aimed to systematically compare arterial/venous thrombosis, fetal loss and stillbirth in pregnant women with systemic lupus erythematosus (SLE), primary anti-phospholipid syndrome (PAPS) and secondary anti-phospholipid syndrome (SAPS).MethodsOnline databases were carefully searched for relevant publications comparing SLE with PAPS and/or SAPS in pregnancy. Studies were included if: they compared SLE with APS [SLE versus PAPS or SLE versus SAPS or SLE versus PAPS and SAPS respectively] in pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
1
13
0
8
Order By: Relevance
“…aPL are associated with thrombosis and pregnancy morbidities, both in primary APS and the APS associated with other autoimmune diseases, including SLE. 33 There are other manifestations, not included in the Sidney classification criteria, 19 that have also been associated with aPL. Consistent with previous studies, 25,28,30,31,34–36 we found that SLE-aPL patients had higher rates of thrombocytopenia than those with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…aPL are associated with thrombosis and pregnancy morbidities, both in primary APS and the APS associated with other autoimmune diseases, including SLE. 33 There are other manifestations, not included in the Sidney classification criteria, 19 that have also been associated with aPL. Consistent with previous studies, 25,28,30,31,34–36 we found that SLE-aPL patients had higher rates of thrombocytopenia than those with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis has even compared pregnant women with SLE vs those with APS. [4] However, previous studies did not systematically focus specifically on the impact of APS on pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, risk of foetal loss with APS has been widely reported in literature [ 28 , 34 ]. A systematic revision with meta-analysis compared foetal loss in 556 pregnant women with SLE versus 385 women with APS; without the appropriate treatment, the group with APS presented a higher risk of foetal loss (RR: 4.49; 95%CI: 2.1–9.6; p = 0.0001) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%